Expanding the Vision for Differentiated Service Delivery: A Call for More Inclusive and Truly Patient-Centered Care for People Living With HIV. (1st February 2021) - Ehrenkranz, Peter; Grimsrud, Anna; Holmes, Charles B.; Preko, Peter; Rabkin, Miriam
Abstract : Background: Simplifying antiretroviral therapy for clinically stable people living with HIV (PLHIV) is important but insufficient to meet their health care needs, including prevention and treatment of tuberculosis and noncommunicable diseases, routine primary care, and family planning. Integrating these services into differentiated service delivery (DSD) platforms is a promising avenue to achieve such coverage. We propose a transition from an HIV-focused "DSD 1.0" to a patient-centered "DSD 2.0" that is inclusive of additional chronic care services for PLHIV. Discussion: The lack of coordination between HIV programs and these critical services puts a burden on both PLHIV and health systems. For individual patients, fractionated services increase cost and time, diminish the actual and perceived quality of care, and increase the risk that they will disengage from health care altogether. The burden on the health system is one of inefficiency and suboptimal outcomes resulting from the parallel systems required to manage multiple vertical programs. Conclusions: DSD 2.0 provides an opportunity for the HIV and Universal Health Coverage agendas—which can seem to be at odds—to achieve greater collective impact for patients and health systems by integrating strong vertical HIV, tuberculosis and family planning programs, and relatively weaker noncommunicable disease programs. Increasing coordination of care for PLHIV will increase the likelihood of achieving and sustaining UNAIDS′ goals of retention on antiretroviral therapy and viral suppression. Eventually, this shift to DSD 2.0 for PLHIV could evolve to a more person-centered vision of chronic care services that would also serve the general population.